ELTV Week-in-Review (African Knowledges and the History Publication since the 1970s, 1990)
A summary of the news for the week beginning at the end of December 1989 and ending on 6 January 1990 (the fourth anniversary of Samuel Kanyon Doe's civilian presidency.
Keywords: Politics; Local News; International News